ROADMAP TATA KELOLA UMKM DAN PENCIPTAAN PRODUK UNGGULAN PADA UMKM DESA WARNASARI, KABUPATEN BANDUNG - Wuryan, Sophiyanto; Nizarlie, Eriene Iranie; Djuarni, Wenny; Baskara, Ika; Sundoro, Aries (POLITEKNIK LP3I JAKARTA, 2025)
The purpose of this community service activity is so that UMKM actors in warnasari village, bandung regency can improve their insight and performance through good governance and how to create superior products.roadmaps are important management tools to improve efficiency, identify opportunities, and direct innovation systematically. Before creating and developing products, business actors need to find out first what is needed, loke or sought by consumers. As an effort to strengthen UMKM efforts in empowering individuals, groups and communities to improve shared welfare. The methods used in this activity are through counseling, training, and mentoring through presentations of materials delivered by the PkM team. This activity is also expected to have a positive impact on UMKM actors and can contribute to economic development.